Penerapan Asas Pembuktian Terbalik dalam Sistem Peradilan Pidana dalam Perkara Pencucian Uang di Indonesia - Sri Herlina; Lutfi Yusup Rahmathoni; Sudiyono Sudiyono; Macario G. Gayeta (CV Rewang Rencang, 2025)
Money laundering is a serious crime that has a major impact on the economic stability and integrity of the country's financial system. This crime is generally associated with predicate offenses, such as corruption, narcotics, and organized crime, to conceal the origin of illicit wealth. In law enforcement, the application of the reverse burden of proof principle is a crucial strategy for overcoming the difficulty of proof. This study examines the application of the reverse burden of proof principle in the Indonesian criminal justice system, particularly in money laundering cases, as outlined in Law Number 8 of 2010. The method used is normative juridical with a conceptual and statutory approach. The results of the study indicate that the application of the reverse burden of proof principle can strengthen efforts to eradicate money laundering, but must still uphold the principle of fair trial and protection of human rights, especially the presumption of innocence. Law Number 8 of 2010 has not comprehensively regulated the standards of proof, verification, and legal impact of this principle, thus creating a vacuum of norms and legal uncertainty. In practice, the accused is only burdened to explain the origin of the wealth, while the prosecutor proves the elements of the crime. However, this shifting burden of proof still raises concerns about violations of the presumption of innocence. Therefore, the application of the reverse burden of proof principle requires more detailed legal regulations and strict supervision so that it is not misused and continues to guarantee legal justice for the accused.